Information and Communication Technology Use on New Generation Teachers’ Job Satisfaction and Psychological Emotion - Xu, Pinglei; Jiang, Ying (Frontiers in Psychology, 2022)
Information and communication technology (ICT) has changed the way teachers work in colleges and universities. Teachers of different ages have different satisfaction and psychological emotions about the changing work way. Based on Person-Job Fit theory, the paper examines the effects of ICT use on teachers' job satisfaction and psychological emotion. The study tests its hypotheses on a sample of 234 new generation teachers in China. Results reveal the positive direct impact of ICT use on job satisfaction and psychological emotion of new generation teachers. Teachers' efficacy plays a partial mediating role and error aversion culture moderates the relationship between ICT use and teachers' efficacy.